2007
DOI: 10.1007/978-3-540-74610-2_15
|View full text |Cite
|
Sign up to set email alerts
|

The Correspondence Between the Logical Algorithms Language and CHR

Abstract: This paper investigates the relationship between the Logical Algorithms formalism (LA) of Ganzinger and McAllester and Constraint Handling Rules (CHR). We present a translation scheme from LA to CHR rp : CHR with rule priorities and show that the metacomplexity theorem for LA can be applied to a subset of CHR rp via inverse translation. This result is compared with previous work. Inspired by the high-level implementation proposal of Ganzinger and McAllester, we demonstrate how LA programs can be compiled into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 12 publications
(25 reference statements)
0
15
0
Order By: Relevance
“…Ganzinger and McAllester (2002) propose a formalism called Logical Algorithms (LA) and prove a meta-complexity result. De Koninck, Schrijvers et al (2007a) establish a close correspondence between CHR and LA (see also Section 6.1.3), allowing the LA meta-complexity result to be applied (indirectly) to a large class of CHR programs. De Koninck, Schrijvers et al (2007a) actually address the metacomplexity of CHR rp programs, an extension of CHR discussed in Section 5.1.3.…”
Section: Ad Hoc Analysismentioning
confidence: 94%
See 2 more Smart Citations
“…Ganzinger and McAllester (2002) propose a formalism called Logical Algorithms (LA) and prove a meta-complexity result. De Koninck, Schrijvers et al (2007a) establish a close correspondence between CHR and LA (see also Section 6.1.3), allowing the LA meta-complexity result to be applied (indirectly) to a large class of CHR programs. De Koninck, Schrijvers et al (2007a) actually address the metacomplexity of CHR rp programs, an extension of CHR discussed in Section 5.1.3.…”
Section: Ad Hoc Analysismentioning
confidence: 94%
“…De Koninck, Schrijvers et al (2007a) have showed how LA programs can easily be translated into CHR rp programs. The opposite only holds for a subset of CHR rp since the LA language lacks the ability to plug in any built-in constraint theory, and also only supports ground constraints (called assertions in LA terminology).…”
Section: Logical Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…-Prolog and Constraint Logic Programming (CLP) programs are translated into CHR ∨ in [10] using Clark's completion. -Logical Algorithms (LA) are mapped into CHR with and without rule priorities in [85]. This are the only known implementations of LA.…”
Section: Embedding Other Formalisms and Languages In Chrmentioning
confidence: 99%
“…Note that in rules ms1 and ms2, the guard prevents the constraints matching the heads from being equal, and so there are no disequality constraints between the CHR constraint identifiers. In (De Koninck et al 2007a) it is derived that the total runtime of this Logical Algorithms program is O(n log n). We defer the complexity analysis of the merge sort algorithm to Section 6.1 where we analyse the CHR rp implementation directly using a new meta-complexity theorem for CHR rp .…”
Section: Its Logical Algorithms Translation Ismentioning
confidence: 99%